The meaning of ecotourism : a New Zealand perspective : a thesis presented in partial fulfilment of the requirements for the degree of Master of Philosophy in Resource and Environmental Planning at Massey University - Browne, Vanessa Louise (Massey University, 1996)
Growing recognition of the negative impacts of conventional mass tourism has been accompanied by an increasing number of tourists seeking tourism that provides opportunities for interaction with the environment. This has created a demand for ecotourism. Ecotourism has been promoted as a means of avoiding the negative environmental impacts while retaining the positive economic impacts of tourism. The definition of ecotourism is far from straightforward. The literature identifies a variety of elements. A consistent definition of ecotourism is required to reduce debate about what ecotourism means, to distinguish between genuine ecotourism operators and those jumping on the ecotourism 'marketing bandwagon', and to inform planners about what is required for successful ecotourism. A 'core' definition of ecotourism has been developed in this thesis based on the common elements identified in recent literature. To test the relevance of these common elements, a selection of 30 people closely involved with tourism in New Zealand were surveyed. Their views support the following definition. Ecotourism is: 'tourism that is environmentally responsible, fosters conservation of natural resources through increased exposure, understanding and education and takes place in the natural environment'. The survey enabled opinion to be gathered on what the ingredients are for a successful ecotourism product. This reinforced the emphasis on education, learning, interaction and participation. The support of local communities and cultures are considered important but secondary ingredients in successful ecotourism. Implementation of a code of ethics across the industry is also favoured by those surveyed.
Keywords: Ecotourism; New Zealand